Permainan Tradisional Ma’boy dalam Meningkatkan Kemampuan Motorik Kasar Pada Anak Usia Dini - Multasam, Dewi; Wahira, Wahira; Asrifan, Andi; Herlina, Herlina (PT. Riset Press International, 2026)
The decline in gross motor skills in early childhood due to the dominance of digital activities and the lack of traditional physical games is a major concern in Indonesian Early Childhood Education (PAUD). This study aims to describe the implementation of traditional Ma'boy game activities in early childhood and to determine the description of gross motor skills of early childhood after being given traditional Ma'boy game activities. Ma'boy is a Bugis-Makassar team game that involves throwing a ball into a pile of used milk cans, running to avoid the opponent's throw, and rearranging the can tower. The study used a quantitative approach with a one-group pre-test post-test design on 30 children aged 4-6 years. Implementation data were collected through a Likert observation sheet (1-5), while gross motor skills were measured with the Test of Gross Motor Development-2 (TGMD-2). Data analysis used descriptive statistics and paired t-test (SPSS 26, α=0.05). The results showed excellent implementation of Ma'boy (mean = 4.72, SD = 0.45), with consistently optimal aspects of equipment preparation/hompimpa (4.80), throwing/running (4.70), and ball arrangement/dodging (4.65). Gross motor skills improved significantly from a pre-test mean of 21.80 (moderate category) to a post-test mean of 33.15 (high category), with an increase of Δ = 11.35 points (t = 14.85, p < 0.001, Cohen's d = 3.12). The ball throwing (Δ = 2.40) and running (Δ = 1.80) subtests showed the highest progress, consistent with the game dynamics. The conclusions confirm that Ma'boy is excellent and effective in improving gross motor skills in early childhood. The implications of this study recommend the integration of Ma'boy into the national Early Childhood Education (PAUD) curriculum as a local cultural intervention to address motor deficits caused by a sedentary lifestyle, with recommendations for larger-scale replication of the study using a control group design.